Case report: Fatal long-term intoxication by 2,4-dinitrophenol and anabolic steroids in a young bodybuilder with muscle dysmorphia - Hermetet, Coralie; Jourdan, Marine; Baert, Alain; Gheddar, Laurie; Ameline, Alice; Kintz, Pascal; Bouvet, Renaud (Frontiers in Public Health, 2024)
A case of chronic intoxication by 2,4-dinitrophenol (2,4-DNP) is reported in a 21-year-old bodybuilder, also known as an abuser of anabolic steroids, who died after ingesting 2 grams of this substance after 6 months of repeated consumption. The bodybuilder presented the triad of symptoms – tachycardia, tachypnoea, profuse sweating – from 6 months before his death, and was hospitalised for multiple organ failure 4 months before his death. Medical staff attributed this serious episode to his consumption of 2,4-DNP. Although the triad of symptoms persisted, he denied continuing to consume 2,4-DNP during consultations with his general practitioner, who therefore looked into a possible diagnosis of endocrine or tumour disorder. The bodybuilder died of multi-organ failure. The autopsy found diffuse visceral congestion and yellowish colouration of integuments. Toxicology demonstrated not only lethal acute 2,4-DNP intoxication (blood concentration was 88 mg/L), but also chronic intoxication (segmental hair concentrations were 5.1 to 25.5 ng/mg). Different anabolic steroids were also identified in the hair. Continued uncontrolled consumption of 2,4-DNP despite the consequences for his health, combined with an obvious preoccupation with his physical appearance, supported the suspected diagnosis of “muscle dysmorphia”, a psychiatric disorder in which dangerous substances are trivialised. Primary care professionals, the first to come into contact with intoxication cases, should receive training on how to detect and manage cases with symptomology that mimics 2,4-DNP use. A large study evaluating the outcomes of acute intoxication cases if “aggressive” management had been immediately implemented may help us determine the optimal course of action that minimises fatalities.